2009
DOI: 10.1111/j.1600-079x.2009.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin induces mitochondrial‐mediated apoptosis in human myeloid HL‐60 cells

Abstract: The role of melatonin in the mediation of apoptotic events has recently gained attention, especially after recent studies have reported that melatonin exerts antiapoptotic actions in normal cells but may activate proapoptotic pathways in some tumor cells. Here, we have evaluated the effect of melatonin on apoptosis in the human leukemia cell line HL-60. Melatonin treatment (1 mm) induced a significant increase in caspase-3 and -9 activities. The effect of melatonin on the activation of caspases was time depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 37 publications
10
127
1
1
Order By: Relevance
“…The authors suggest the same mechanism proposed for RHM (see above), i.e., that melatonin protects by scavenging hydroxyl and peroxyl radicals responsible for the oxidative stress leading to apoptosis (Espino et al 2010). Another recent paper reports that, in human myeloid HL-60 cells, melatonin induces caspase activation accompanied by mitochondrial depolarization, induction of MPT, release of cytochrome C, and apoptosis (Bejarano et al 2009). These findings match our results in RLM, although the authors do not report any effect regarding possible oxidative stress induced by melatonin.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The authors suggest the same mechanism proposed for RHM (see above), i.e., that melatonin protects by scavenging hydroxyl and peroxyl radicals responsible for the oxidative stress leading to apoptosis (Espino et al 2010). Another recent paper reports that, in human myeloid HL-60 cells, melatonin induces caspase activation accompanied by mitochondrial depolarization, induction of MPT, release of cytochrome C, and apoptosis (Bejarano et al 2009). These findings match our results in RLM, although the authors do not report any effect regarding possible oxidative stress induced by melatonin.…”
Section: Discussionmentioning
confidence: 71%
“…It has also been found that the indolamine induces mitochondrial-mediated apoptosis in human myeloid HL-60 cells (Bejarano et al 2009) but reduces this process in human leukocytes (Espino et al 2010). The differential actions exhibited by melatonin on mitochondria and apoptosis in normal and cancer cells were also previously reported in a review article (Sainz et al 2003).…”
Section: Introductionmentioning
confidence: 66%
“…The intrinsic and extrinsic pathways are connected by the caspase-8-mediated cleavage of the pro-apoptotic Bcl-2 family member BH3 interacting-domain death agonist (Bid), which translocates to mitochondria to trigger the release of cytochrome C. Melatonin increases the activation and association of Bax and Bid and is associated with a detectable rise in the expression of both proteins [11,49]. For example, melatonin upregulates Bax and the conversion of caspase-3 to cleaved form in human colorectal cancer cells [15].…”
Section: Activation Of Intrinsic and Extrinsic Apoptotic Pathwaysmentioning
confidence: 99%
“…In this sense, melatonin seems to be able to block ETC complexes and decrease ATP production (Wang et al, 2013), as well as activate the intrinsic apoptotic pathway (Bejarano et al, 2009). Furthermore, antioxidant and scavenger capacities of melatonin may also intervene (Espino et al, 2010;Luchetti et al, 2010).…”
Section: Cancermentioning
confidence: 99%